PENGARUH MEDIA PASIR DAN LUMPUR PADA PERTUMBUHAN JAGUNG (Zea mays) - Sri Mukminati Nur (Universitas Cokroaminoto Palopo, 2022)
This study is an experimental study, using a completely randomized design with 3 treatments with 5 repetitions each. The problem in this research is how much influence the mud and sand media have on the growth of corn (Zea mays), the data collection techniques in this study are observation and documentation. While thequantitative data analysis technique is equipped with a growth parameter table, average percentage and BNT test. The results of this study that the growth of corn seeds using mud media on stem height with an average value of 28.62 with a BNT value of 88.395, stem diameter with an average value of 4.24 with a BNT value of 10.65 and an average number of leaves 9 with a BNT value of 23.46. While the growth of corn seeds using sand media on stem height with an average value of 31.38 with a BNT value of 59.34, stem diameter with an average value of 4.36 with a BNT value of 10.95 and the number of leaves with an average value 9 with a BNT value of 23.46. The two planting media used, the sand planting media, are the faster growing corn seeds. Sand textured soil is very easy to cultivate, this medium has good aeration (availability of air voids) and drainage, has a relatively small cumulative surface area, so that the ability of sprout roots to penetrate sandy textured soil is very easy and causes sprouts to grow very quickly.